APLIKASI COMMODITY SYSTEM ASSESSMENT METHOD (CSAM) DALAM DISTRIBUSI SAWI PAKCOY (Brassica rapa L) DARI PETANI DI KECAMATAN BATURITI KE PENGECER - Eka Suwarjana, Putu; Lani Triani, I G.A.; Admadi H, Bambang (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 3 No 4 (2015): Desember, 2015)
The aimed of research were to determine the type of pakcoy mustards distribution lines from farmers in Baturiti District to retailers to determine the distribution lines and postharvest handling of pakcoy mustard from farmers in Baturiti District to retailers, and to determine the impact of postharvest loss and pesticide residues in pakcoy mustard from farmers in Baturiti District to retailers. The study used a survey method with the application of Commodity System Assessment Method in the form of questionnaire distributed to farmers, collectors, wholesalers, and retailers pakcoy mustard. There were three distribution lines of pakcoy mustard, line 1 (farmers ----retailers), lane II (farmers ---- collectors --- retailers), lane III (farmers ---- collectors ---- wholesalers ---- retailers). Postharvest handling at the farm level include of harvesting, sorting, packaging, and transporting. Postharvest handling at the level of collector and wholesalers includes the weighing and transporting, postharvest handling at the retailer level includes inspection, packaging, and display. The impact on postharvest loss pakcoy mustard at farm level was at harvesting level reached 13%, at collectors level was in the process of transporting up to 2%, at the level of big traders on transporting reached 2%, and at the retail level on the display reached 9%.
Keywords: 81